ASSESSING POST-LOCKDOWN PSYCHOLOGICAL PREPAREDNESS FOR RESUMPTION AMONG UNIVERSITY STUDENTS IN NIGERIA: THE ROLE OF ANXIETY AND SOCIAL SUPPORT - Chovwen, Catherine Oluwatoyin; Adu, Richard Akinjide; Morakinyo, Luqman Adekunle (African Journal of Social and Behavioural Sciences, 2022)
Psychological preparedness is critical for one to be able to successfully adapt to life changes/challenges. Previous studies focused more on psychological preparedness during disasters. There is dearth of literature on students’ psychological preparedness for changes that may occur in the course of their studies. Therefore, this study examines the role of anxiety and social support in psychological preparedness among university students in Nigeria. Cross-sectional survey design via online questionnaire administration to 676 respondents from 30 universities across the 6 geo-political zones of Nigeria was utilised in this study. The questionnaire comprised of anxiety (α = 0.84), social support (α = 0.90) and psychological preparedness (α = 0.81) scales. Data were analysed using descriptive statistics, Pearson Product Moment Correlation, Hierarchical Multiple Regression Analysis and Analysis of Variance. Participants’ age ranged from 17 to 32 years. , 72.6% were males while 94.4% attended public universities. There was significant negative relationship between anxiety and psychological preparedness (r = -.15, p < .01). Whereas significant positive association occurred between social support and psychological preparedness (r = .23, p < .01). Anxiety and social support jointly predicted psychological preparedness significantly [R2 = .13, F(4,671) = 24.15, p < .01]. There was significant main effect of social support on psychological preparedness among participants, [F (1,672) = 13.96, p < .01]. Anxiety and social support jointly predicted participants’ psychological preparedness. Low level of anxiety and high level of social support enhanced the psychological preparedness of the participants.